1971
DOI: 10.1038/bjc.1971.50
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Pattern in African Gold Miners

Abstract: SUMMARY.-The incidence of cancer among the African workers on the gold mines of South Africa has been studied for the period 1964-68. Considering the degree of selection to which they are subjected, the crude cancer rate was unexpectedly high.The most common cancers were those of the liver, the oesophagus, the respiratory system and the bladder. locally at the recruiting centre, the second on arrival at the transit station and the third at the mine to which the recruits have been assigned-these latter two bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…It seems clear, however, that agricultural exposure may not be unique in this regard, as a number of studies have implicated asbestos (Robertson et al, 1971), wood dust (Brinton et al, 1976;Decouffle et al, 1977), leather dust (Decouffle et al, 1977) and heavy metal exposure (Decouffle et al, 1977;Axelson et al, 1978) as factors with possible associations with myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…It seems clear, however, that agricultural exposure may not be unique in this regard, as a number of studies have implicated asbestos (Robertson et al, 1971), wood dust (Brinton et al, 1976;Decouffle et al, 1977), leather dust (Decouffle et al, 1977) and heavy metal exposure (Decouffle et al, 1977;Axelson et al, 1978) as factors with possible associations with myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Early evidence had pointed to the Zulu being especially affected by this cancer (Robertson et al, 1971), whereas nowadays KwazuluNatal rates (CIR 4.8) fall well below the average rate for all miners (9.4) and below half their own rate of 12.7 in 196412.7 in -79 (McGlashan et al, 1982.…”
Section: Spatial and Temporal Distribution Of Cancer Sitesmentioning
confidence: 99%
“…
Summary.-The 5-year study of cancer in black gold miners, 1964-68, previously reported (Robertson et al, 1971) has now been extended for a separate 8-year period, 1972-79. This allows analyses of all cancers together and of 6 less common sites of cancer severally: lymphosarcomas, colon and rectum, leukaemia, stomach, pancreas and buccal cavity and also of those too rare to classify.
…”
mentioning
confidence: 97%
“…Finally, temporal change over the years 1964-79 shows a significant decrease overall (P <0.01) in cases of lymphosarcomas and colo-rectal cancers and an increase (P<0.05) in stomach cancer. The rare tumour, Kaposi's sarcoma, has also decreased significantly between the 2 periods studied.ANALYSES published by Robertson et al, (1971), Harington et al (1975 and Bradshaw et al (1982) have considered the spatial and temporal patterns of the 4 most common sites of cancer recorded among black gold miners recruited from homes in, respectively, 11 and 10 territories in 2 consecutive 8-year periods, 1964-1971 and 1972-1979 (see Fig. 1 for total gold-mine labour force from each home territory).…”
mentioning
confidence: 99%
See 1 more Smart Citation